KARAKTERISTIK GETARAN DALAM BENTUK WAVEFORM DAN SPEKTRUM MELALUI TRANSFORMASI FOURIER - Salman; I Dewa Ketut Okariawan; Nurchayati; Arif Mulyanto; Emmy Dyah Sulistyowati (Jurusan Teknik Mesin dan Industri, Fakultas Teknik, Universitas Mataram, 2025)
The analysis of machine vibration is therefore essential for predictive maintenance and condition monitoring. Modern approaches, ranging from time-domain measurements of acceleration, velocity, and displacement to frequency-domain and modal analysis. This study investigates the vibration characteristics of rotating equipment in a manufacturing environment, focusing on identifying dominant frequencies, evaluating amplitude trends, and assessing overall machine condition. Data collected from accelerometers mounted on a centrifugal pump were processed using time-domain and frequency-domain techniques. The results highlight clear signatures of imbalance and bearing wear, demonstrating the value of predictive maintenance based on vibration monitoring. As the result the amplitude–frequency spectrum demonstrates that the machine is primarily influenced by rotational imbalance, with minimal evidence of high-frequency faults.